Design and synthesis of sulfur-containing butylated hydroxytoluene: antioxidant potency and selective anticancer agent - Ahmad, Mohd H.; Abd Rahman, Noorsaadah; Kadir, Farkaad Abdul; Al-Ani, Lina Adnan; Hashim, Najihah Mohd; Yehye, Wageeh Abdulhadi (Springer Verlag, 2019)
Abstract: In the present study, a series of multipotent antioxidants (MPAOs), namely sulfur-containing BHT (S-BHT), derivatives were rationally designed and synthesized, and their inhibitory activities against free radicals and human cancer cell lines, HT29 (colon cancer) and MCF7 (breast cancer) were further evaluated. The experimental results showed that the Six out-of-eight S-BHT compounds had excellent antioxidant activity against DPPH radical with major enhancement compared to BHT. Among them, compounds 2b, 2a and 3b attained over 45% lower IC50 values than BHT. In vitro cytotoxicity, MTT assay was carried out using two human cancer cell lines, HT29 (colon cancer) and MCF7 (breast cancer) in addition to their non-tumorigenic counterparts to explore selectivity. In line with antioxidant activity, compounds 2a and 2b displayed the highest cytotoxicity effect on both cancer types. Interestingly, 2b not only exhibited superior cancer inhibition but also scored high selectivity index (SI = 5.2, 12.5) in colon and breast tissues, respectively, exceeding that of the standard chemotherapeutic drugs used 5-Fluorouracil (5-FU) and Tamoxifen (Tmx), with lower IC50 values. The results indicated that the symmetric S-BHT derivatives were significantly enhanced by the antioxidant potency and their ability as useful and promising selective anticancer agents. Graphic abstract: A series of sulfur-containing phenols (S-BHT) as multipotent antioxidants structure have been rationally designed and synthesized by the combination of the antiradical activity of the most well-known phenol moiety, butylated hydroxytoluene (BHT, primary antioxidant) with the antiperoxide (secondary antioxidant) and anti-proliferative fragments, sulfur-containing groups into one structure aiming to enhance scavenging ability and antiproliferative activity of the radicals. Accordingly, the bioactivity of S-BHT was analysed by antioxidant and anticancer in vitro studies and demonstrated remarkable cancer inhibition rates along with significant cytotoxicity and selectivity against HT29 and MCF7 cancer cell lines. This work efficiently sets the ground for eminent sulfur-containing phenols developed based on a well-known standard antioxidant BHT, with features superior to common drawbacks faced in cancer therapeutic approaches, in addition to the great potential holding as selective and biocompatible agent for cancer applications.[Figure not available: see fulltext.] © 2019, Indian Academy of Sciences.